Method for synthesizing mesoporous nano-sized zeolite beta by hydrothermal treatment and its use

Synthesis of nano-sized mesoporous zeolite β by hydrothermal treatment has solved the problems of low catalyst activity and inactivation in the prior art, and improved catalyst performance and reduced process costs have been achieved.

CN116395708BActive Publication Date: 2025-05-02SAUDI ARABIAN OIL CO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310018026.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-01-06
Filing Date
2023-01-06
Publication Date
2025-05-02
Estimated Expiration
2043-01-06

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently synthesize beta zeolite catalysts with nano-size and mesoporous structures, resulting in low catalytic activity and possible inactivation of the catalyst.

Method used

Synthesize nano-sized mesoporous zeolite β by hydrothermal treatment, the method includes mixing silica, aluminum source, tetraethylammonium hydroxide and water to form an aluminum silicate fluid gel without drying and calcining the zeolite, and hydrothermal treatment in an autoclave to produce a mesoporous zeolite β with improved pore structure and crystallinity.

Benefits of technology

It improves the catalytic activity and stability of the catalyst, enhances the diffusion ability of macromolecules in the zeolite structure, and reduces process costs and complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395708B_ABST
    Figure CN116395708B_ABST
Patent Text Reader

Abstract

Nanosized mesoporous zeolite beta compositions and synthesis methods and uses of the nanosized mesoporous zeolite beta. Nanosized mesoporous zeolite beta is synthesized using hydrothermal treatment without drying and calcining the zeolite before or after the hydrothermal treatment. A method for hydrocracking hydrocarbon feedstock using the nanosized mesoporous zeolite beta is also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates generally to nano-sized mesoporous zeolite compositions. More specifically, embodiments of the present disclosure relate to the synthesis of such compositions using hydrothermal treatment and the uses of such compositions. Background Art

[0002] Beta zeolite is a crystalline aluminum silicate that is widely used in heavy oil conversion processes such as hydrocracking and fluid catalytic cracking processes. In particular, beta zeolite is used in such processes based on pore structure, stability and acidity considerations. The feedstock for these processes is a portion of crude oil with an initial boiling point of 350°C and an average molecular weight range of about 200 to 600 or more. As the properties of crude oil deteriorate year by year and the demand for clean fuels and petrochemical products continues to increase, it is necessary to use various processes and catalysts (such as zeolites) to convert more heavy oil. Summary of the invention

[0003] Crude oil (e.g., heavy crude oil) can be hydrotreated and subsequently hydrocracking catalysts are used to remove undesirable components such as sulfur, nitrogen and metals, and high molecular weight hydrocarbons (complex aromatics or unsaturated hydrocarbons) are converted into naphtha, kerosene, gasoline, diesel or high quality lubricating oils. The catalyst used for hydrotreating has two functions: cracking high molecular weight hydrocarbons and hydrogenating unsaturated molecules. Conventional beta zeolite (also referred to as "zeolite beta") has a relatively small pore size (less than 2 nm), which does not allow the macromolecules of the heavy oil conversion process to diffuse to the active sites located inside the zeolite and react thereon, thereby negatively affecting the performance of the beta zeolite catalyst. This results in low catalytic activity and possible deactivation of the catalyst.

[0004] The mass transfer of molecules can be enhanced by increasing the pore size of the zeolite and reducing the particle size of the zeolite, thereby improving the catalyst performance. In some cases, ordered mesoporous aluminum silicates with larger pore sizes can be used to synthesize catalysts with relatively large pore sizes. In addition, the particle size of the catalyst can be reduced during the synthesis process to increase the external surface and shorten the diffusion path of the molecules, thereby improving the catalyst performance. However, it is difficult to synthesize catalysts with nano-sized particles and mesopores by existing technologies.

[0005] Existing processes for synthesizing nanosized zeolite beta have various problems, such as irregularities in the zeolite catalyst due to the need for ion exchange and separation steps to obtain the H-type zeolite product or the proton zeolite form, aggregation of nanosized particles, and reduced yield of the final product. Existing processes generally require calcining the zeolite beta prior to additional treatment to remove all templates or structure directing agents (SDAs) used for zeolite synthesis. Such methods can increase the pore volume and average pore size of the zeolite, but can also result in a decrease in crystallinity, which indicates partial destruction of the zeolite structure.

[0006] Embodiments of the present disclosure include methods for synthesizing nano-sized zeolite beta with mesopores (referred to as "meso-nano zeolite beta") using hydrothermal treatment without drying and calcining the zeolite. In addition, the method can synthesize nano-sized beta zeolite without using a structure directing agent (SDA) such as cetyltrimethylammonium bromide (CTAB). Meso-nano zeolite beta can be used as a catalyst in heavy oil conversion processes, such as hydrocracking and fluid catalytic cracking.

[0007] As used in this disclosure, the term "mesopore" refers to the distribution of pore sizes in the zeolite structure that are greater than 2 nanometers (nm) and less than or equal to 50 nm. The term "mesopore" is different from "micropores" (pore size distribution in the range of 0.5 nm to less than 2 nm) and "macroporous" (pore size distribution greater than 50 nm).

[0008] In one embodiment, a method for synthesizing a nanosized mesoporous zeolite beta composition is provided. The method includes mixing silica, an aluminum source, tetraethylammonium hydroxide, and water to form an aluminum silicate fluid gel, and heating the aluminum silicate fluid gel at a first temperature for a first period of time to form a zeolite beta product. The method also includes hydrothermally treating the zeolite beta product at a pressure and a second temperature for a second period of time to produce the nanosized mesoporous zeolite beta composition, whereby the zeolite beta product is not calcined prior to the hydrothermal treatment.

[0009] In some embodiments, the nano-sized mesoporous zeolite beta composition has a pore volume of 1.0 milliliters per gram (ml / g) to 1.5 ml / g. In some embodiments, the nano-sized mesoporous zeolite beta composition has a pore size of 15 nanometers (nm) to 50nm. In some embodiments, the nano-sized mesoporous zeolite beta composition has a particle size of 10 nanometers (nm) to 100nm. In some embodiments, the silica is fumed silica. In some embodiments, the aluminum source is alumina. In some embodiments, the zeolite beta product is hydrothermally treated at pressure and a second temperature for a second time period to produce a treated zeolite beta product. In some embodiments, the first temperature is in the range of 100°C to 150°C, and the first time period is in the range of 2 days to 7 days. In some embodiments, the pressure is in the range of 1 bar to 5 bars, the second temperature is in the range of 400°C to 600°C, and the second time period is in the range of 0.5 hours to 4 hours. In some embodiments, the method includes: filtering the nano-sized mesoporous zeolite beta composition; after filtering, washing the nano-sized mesoporous zeolite beta composition product; after washing, drying the nano-sized mesoporous zeolite beta composition at a third temperature for a third time period; and after drying, calcining the nano-sized mesoporous zeolite beta composition at a fourth temperature for a fourth time period to produce a nano-sized mesoporous zeolite beta composition. In some embodiments, the third temperature is in the range of 80°C to 150°C, and the third time period is in the range of 3 hours to 8 hours. In some embodiments, the fourth temperature is in the range of 500°C to 600°C, and the fourth time period is in the range of 3 hours to 8 hours.

[0010] In another embodiment, a method for hydrocracking a hydrocarbon feedstock is provided. The method comprises: contacting the hydrocarbon feedstock with a catalyst containing a nanosized mesoporous zeolite beta composition under reaction conditions to convert a product stream containing at least 20 weight percent hydrocarbons having 1 to 4 carbon atoms. The nanosized mesoporous zeolite beta composition is synthesized by a method comprising the following steps, including: mixing silica, an aluminum source, tetraethylammonium hydroxide, and water to form an aluminum silicate fluid gel, and heating the aluminum silicate fluid gel at a first temperature for a first time period to form a zeolite beta product. The method also includes hydrothermally treating the zeolite beta product at a pressure and a second temperature for a second time period to prepare the nanosized mesoporous zeolite beta composition, such that the zeolite beta product is not calcined prior to the hydrothermal treatment.

[0011] In some embodiments, the nano-sized mesoporous zeolite beta composition has a pore volume of 1.0 milliliters per gram (ml / g) to 1.5 ml / g, and a pore size of 15 nanometers (nm) to 50 nm. In some embodiments, the nano-sized mesoporous zeolite beta composition has a particle size of 10 nanometers (nm) to 100 nm. In some embodiments, the silica is fumed silica. In some embodiments, the aluminum source is alumina. In some embodiments, the zeolite beta product is hydrothermally treated at a pressure and a second temperature for a second time period to produce a treated zeolite beta product. In some embodiments, the first temperature is in the range of 100°C to 150°C, and the first time period is in the range of 2 days to 7 days. In some embodiments, the pressure is in the range of 1 bar to 5 bars, the second temperature is in the range of 400°C to 600°C, and the second time period is in the range of 0.5 hours to 4 hours. In some embodiments, the hydrocarbon feedstock is a heavy fraction having a boiling point greater than or equal to 540°C.

[0012] In another embodiment, a nano-sized mesoporous zeolite beta composition is provided. The composition comprises: a plurality of nano-sized mesoporous zeolite particles, each of the plurality of particles having a particle size of 10 nanometers (nm) to 100 nm, a pore volume of 1.0 milliliters / gram (ml / g) to 1.5 ml / g, and a pore size of 15 nanometers (nm) to 50 nm. A plurality of nano-sized mesoporous zeolite particles are synthesized by a method comprising the following steps: mixing silica, an aluminum source, tetraethylammonium hydroxide, and water to form an aluminum silicate fluid gel, and heating the aluminum silicate fluid gel at a first temperature for a first time period to form a zeolite beta product. The method also includes hydrothermally treating the zeolite beta product at a pressure and a second temperature for a second time period to prepare the nano-sized mesoporous zeolite beta composition, so that the zeolite beta product is not calcined before the hydrothermal treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a block diagram of a method for synthesizing meso-nano zeolite beta according to an embodiment of the present disclosure; and

[0014] Figure 2 Schematic diagram of a hydrothermal treatment apparatus or synthesis of meso-nano zeolite β according to an embodiment of the present invention. DETAILED DESCRIPTION

[0015] The present disclosure will be more fully described with reference to the accompanying drawings, which illustrate embodiments of the present disclosure. However, the present disclosure may be embodied in many different forms and should not be construed as being limited to the embodiments shown. Instead, these embodiments are provided so that the present disclosure will be thorough and complete and will fully convey the scope of the present disclosure to those skilled in the art.

[0016] Embodiments of the present disclosure include meso-nano zeolite beta compositions and methods for synthesizing meso-nano zeolite beta and uses thereof. The method includes synthesizing meso-nano zeolite beta using hydrothermal treatment, without the need to dry and calcine the zeolite before the hydrothermal treatment. Advantageously, the synthesized meso-nano zeolite beta has improved crystallinity and mesoporosity compared to conventional beta zeolites and synthesis methods. The improved crystallinity and mesoporosity can result in improved catalytic performance in heavy oil conversion processes (such as hydrocracking and fluid catalytic cracking). In addition, the synthesis process described in the present disclosure results in reduced cost and complexity (e.g., the number of synthesis steps) compared to conventional processes. The resulting meso-nano zeolite beta composition is an H-type meso-nano zeolite beta.

[0017] Figure 1 A process 100 for synthesizing meso-nano zeolite beta according to an embodiment of the present invention is described. Initially, nano-sized zeolite beta can be synthesized from a gel composition (block 102). The gel composition can have the following molar ratios: about 20 moles to about 500 moles of fumed silica (SiO 2 ); about 15 mol to about 40 mol of tetraethylammonium hydroxide (C 8 H 21 NO, referred to herein as "TEAOH") and 1 mol of aluminum (e.g., as γ-alumina (γ-Al 2 O 3 ) and about 17 moles to about 700 moles of H 2 In such an embodiment, the fumed silica may be 200, available from Evonik Industries AG of Essen, German. Degussa. In other embodiments, the silica can be colloidal silica. In some embodiments, the aluminum source is metallic aluminum. In some embodiments, the aluminum source can be aluminum powder. In some embodiments, TEAOH and H 2 The TEAOH solution may be provided as a TEAOH solution. In some embodiments, the concentration of the TEAOH solution may be in the range of 20 wt % (wt %) to 40 wt %. For example, the TEAOH solution may be a 35 wt % (wt %) TEAOH aqueous solution, such as obtained from MillporeSigma of Burlington, Massachusetts, USA. In some embodiments, in addition to the water in the TEAOH aqueous solution, additional water (H 2 O) to achieve the desired molar amount.

[0018] Nano-sized zeolite beta can be synthesized by preparing a slurry from fumed silica and an aqueous TEAOH solution (box 104) in the above-mentioned molar ratio. Next, alumina can be dissolved in the aqueous TEAOH solution and added to the slurry to form an aluminum silicate fluid gel (box 106). The aluminum silicate fluid gel can be stirred for a period of about 4 hours at ambient temperature (box 108). The aluminum silicate fluid gel can then be transferred to an autoclave, such as a polytetrafluoroethylene (PTFE) lined stainless steel autoclave. The aluminum silicate fluid gel can be allowed to crystallize in an autoclave at a temperature of 100° C. to 150° C. in a static state for a period of 2 to 7 days (box 110), thereby producing a crystalline nano-sized zeolite beta.

[0019] The crystallized nano-sized zeolite beta can be transferred to a hydrothermal treatment device without drying, calcining or both (box 112). The crystallized nano-sized zeolite beta can be hydrothermally treated (box 114) using steam at a pressure of 1 bar to 5 bars and a temperature of 400°C to 600°C for about 0.5 hours to 5 hours to produce meso-nano zeolite beta. In some embodiments, the meso-nano zeolite beta produced after hydrothermal treatment can be directly used in catalyst applications without any washing, drying or calcining. For example, the meso-nano zeolite beta produced after hydrothermal treatment can be separated or filtered and directly used in catalyst applications. In such an embodiment, the method for synthesizing meso-nano zeolite beta can consist of the above steps (i.e., 102, 112, and 114).

[0020] In other embodiments, the hydrothermally treated product may be washed 2 to 4 times with deionized water, dried in an oven at a temperature of 80°C to 150°C for a period of about 3 hours to 8 hours, and calcined in an oven at 500°C to 600°C for a period of about 3 hours to 8 hours.

[0021] Figure 2 An exemplary hydrothermal treatment apparatus 200 according to an embodiment of the present disclosure is depicted. The hydrothermal treatment apparatus 200 may include a vessel 202 containing crystalline nano-sized zeolite beta 204, a needle valve 206, a pressure gauge 208, a heater 210, and a temperature monitor and controller 212. The heater 210 heats the vessel 202 and is controlled by the temperature monitor and controller 212. The controller 212 may monitor (directly or indirectly) the temperature within the vessel 202. The pressure gauge 208 provides an indication of the steam pressure within the vessel 202. The steam pressure within the vessel 202 may be controlled by the needle valve 206. For example, if the steam pressure is greater than a desired value, the needle valve may be opened to release excess steam and reduce the pressure.

[0022] pass Figure 1 The meso-nano zeolite beta produced by the methods shown and described below may have the following properties: a particle size of 10 nanometers (nm) to 100 nm; a surface area greater than 510 square meters per gram (m2 / g), for example, at 510m 2 / g to 567m 2 / g range; pore volume is 1.0 milliliters per gram (ml / g) to 1.5 ml / g; pore diameter is 15nm to 50nm; and relative crystallinity is greater than 100%, for example, in the range of 108% to 139%. As used in this disclosure, pore volume refers to the total pore volume measured. In addition, by Figure 1 The meso-nano zeolite beta prepared by the method shown and described below is meso-nano zeolite beta of type H.

[0023] The combination of nanoparticle size and mesoporosity can enhance the diffusion of macromolecules within the zeolite structure, since the prepared meso-nano zeolite beta has larger accessible active sites and faster and easier mass transfer. In addition, the combination of nanoparticle size and mesoporosity increases the hydrothermal stability and external surface area compared to existing zeolite catalysts, which will improve the catalyst's selective activity for heavy oil conversion processes.

[0024] The meso-nano zeolite beta synthesized according to the method of the present disclosure and having the properties described in the present disclosure can be used in a method for hydrocracking hydrocarbon feedstocks. According to an embodiment of the present disclosure, a method for hydrocracking a hydrocarbon feedstock using meso-nano zeolite beta may include contacting the hydrocarbon feedstock with a catalyst containing meso-nano zeolite beta under reaction conditions to produce a product stream. In some embodiments, the hydrocarbon feedstock may include a "heavy" fraction with a boiling point of 540°C or above (540°C+). Compared with conventional catalysts and processes, meso-nano zeolite beta can increase the conversion rate of 540°C+ fractions into lighter fractions (e.g., paraffin and cycloparaffin fractions), thereby increasing olefin production and profitability. Lighter fractions can be more easily converted by steam cracking to produce higher yields of light olefins.

[0025] The reaction conditions for hydrocracking the hydrocarbon feedstock may include a temperature range of 250°C to 420°C, a liquid hourly space velocity range of 0.5 to 10 per hour, and a hydrogen to oil volume ratio range of 500 to 2000. The reaction conditions may include a temperature range of 250°C to 400°C, or 250°C to 375°C, or 300°C to 420°C, or 325°C to 400°C. The reaction conditions may include a liquid hourly space velocity range of 0.5 to 8 per hour, or 0.5 to 5 per hour, or 0.5 to 2 per hour. The reaction conditions may include a hydrogen to oil volume ratio range of 500 to 1800, or 500 to 1500, or 700 to 1800, or 700 to 1500. In certain embodiments, the hydrocarbon feedstock has at least 60% by weight of components with a boiling point range of 180°C to 540°C. In certain embodiments, the hydrocarbon feedstock has at least 70% by weight of components with a boiling point range of 180°C to 540°C. In certain embodiments, the hydrocarbon feedstock has at least 80 wt% components boiling in the range of 180°C to 540°C.

[0026] Example

[0027] The following examples are included to illustrate embodiments of the present disclosure. It will be appreciated by those skilled in the art that the techniques and compositions disclosed in the following examples represent techniques and compositions found to function well in the practice of the present disclosure and therefore can be considered to constitute modes of its practice. However, it will be appreciated by those skilled in the art, in light of the present disclosure, that many changes may be made in the specific embodiments disclosed without departing from the spirit and scope of the present disclosure and still obtaining similar or similar results.

[0028] Exemplary meso-nano zeolite beta synthesized by embodiments of the present disclosure were compared to a reference conventional nano zeolite beta (referred to as "reference-nano beta") and a reference hydrothermally treated nano-sized zeolite beta (referred to as "reference-HT-nano beta").

[0029] Conventional nano zeolite beta ("reference-nano beta") and reference hydrothermally treated nano-sized zeolite beta ("reference-HT-nano beta") were produced using the following process:

[0030] 1. Use a molar composition of 30 mol TEAOH:50 mol SiO 2 :Al 2 O 3 :750 mol H 2Nano-sized zeolite beta was synthesized from a precursor solution of 100 μm / min. O. The solution was prepared by dissolving 0.27 g of metallic aluminum powder in 25 g of 35% TEAOH solution and stirring the aluminum-TEAOH mixture at room temperature for 1 hour to form a clear solution. A slurry was formed by mixing 15 g of fumed silica with 38 g of 35% TEAOH solution. The slurry was mixed with the aluminum-TEAOH mixture to form an aluminum silicate gel. The aluminum silicate gel was stirred in a beaker at room temperature for 4 hours. The aluminum silicate gel was transferred to an autoclave with a PTFE liner and heated in an oven at a temperature of 140°C for 3 days.

[0031] 2. The autoclave was quenched and the solid product was separated from the liquid using a centrifuge at 12,000 revolutions per minute (rpm). The separated solid was washed with distilled water, dried at 110° C. for 8 hours, and then calcined at 600° C. for 4 hours to prepare conventional nano zeolite beta (“reference-nano beta”).

[0032] 3. The conventional nano-sized zeolite β was then hydrothermally treated in a hydrothermal treatment apparatus at 1 bar gauge pressure and 550° C. for 1 hour to prepare a reference hydrothermally treated nano-sized zeolite β (“reference-HT-nano-β”).

[0033] Exemplary meso-nano zeolite beta was synthesized according to the following embodiments of the present disclosure:

[0034] 1. Use a molar composition of 30 mol TEAOH:50 mol SiO 2 :Al 2 O 3 :750 mol H 2 Nano-sized zeolite beta was synthesized from a precursor solution of 100 μm / min. The solution was prepared by dissolving 0.27 g of metallic aluminum powder in 25 g of a 35% TEAOH solution and stirring the aluminum-TEAOH mixture at room temperature for 1 hour to form a clear solution. A slurry was formed by mixing 15 g of fumed silica with 38 g of a 35% TEAOH solution. The slurry was mixed with the aluminum-TEAOH mixture to form an aluminum silicate gel. The aluminum silicate gel was stirred in a beaker at room temperature for 4 hours. The aluminum silicate gel was transferred to an autoclave with a PTFE liner and heated in an oven at a temperature of 140° C. for 3 days.

[0035] 2. Nano zeolite beta products from autoclave Hydrothermal treatment was performed at three different temperatures for 1 hour at 1 bar gauge pressure in a hydrothermal treatment device to synthesize three products. Nano zeolite beta was hydrothermally treated at 500°C to produce an exemplary meso-nano zeolite beta called "NZ-HT-1". Nano zeolite beta was hydrothermally treated at 550°C to produce an exemplary meso-nano zeolite beta called "NZ-HT-2". Finally, nano zeolite beta was hydrothermally treated at 600°C to produce an exemplary meso-nano zeolite beta called "NZ-HT-3".

[0036] The relative crystallinity of various zeolite betas was analyzed by x-ray diffraction (XRD) using a diffractometer, such as the Rigaku Ultima IV multifunctional diffractometer with a copper x-ray tube from Rigaku Corporation (Tokyo, Japan). The scanning range was set between 2° and 50° of the 2θ Bragg angle, with a step length of 0.04° and a total counting time of 1° per minute. The percentage crystallinity was calculated by comparing the area under the strongest diffraction peak with the area of ​​the pattern of the reference zeolite beta, by PANalytical High Score Plus software derived from Malvern Panalytical of Mavern (Worcestershire, United Kingdom).

[0037] The properties of conventional nano zeolite beta ("reference-nano beta"), reference hydrothermally treated nano-sized zeolite beta ("reference-HT-nano beta") and meso-nano zeolite beta NZ-HT-1, NZ-HT-2 and NZ-HT-3 are summarized in Table 1 below:

[0038] Table 1: Properties of reference nano-zeolite β and meso-nano-zeolite β

[0039]

[0040] As shown in Table 1, the pore volume of meso-nano zeolite β is significantly increased compared to conventional zeolite β, indicating that more mesopores are generated. In addition, the crystallinity of meso-nano zeolite β is significantly higher, indicating that the preservation of the zeolite structure during hydrothermal treatment is improved. Calcination of the reference-HT-nano β before hydrothermal treatment removes the TEAOH template. Unlike the reference-HT-nano β, the TEAOH template is preserved in the zeolite cages and channels during hydrothermal treatment. The preserved template retains the zeolite structure and improves the zeolite crystallinity.

[0041] In the present disclosure, ranges may be expressed as from about one particular value to about another particular value, or both. When such a range is expressed, it should be understood that another embodiment is from one particular value to another particular value, or both, and all combinations within the range.

[0042] Based on this specification, it will be clear to those skilled in the art that further modifications and alternative embodiments of various aspects of the present disclosure. Therefore, it is understood that this specification is illustrative only, and the purpose is to teach those skilled in the art to implement the general manner of the embodiments described in the present disclosure. It should be understood that the forms shown and described in the present disclosure will be used as examples of embodiments. The elements and materials shown and described in the present disclosure can be replaced by other elements and materials, parts and processes can be reversed or omitted, and certain features can be used independently, all of which are obvious to those skilled in the art, thanks to this specification. Without departing from the spirit and scope of the present disclosure as described in the following claims, the elements described in the present disclosure can be changed. The titles used in the present disclosure are only for organizational purposes and are not intended to be used to limit the scope of the specification.

Claims

1. A method for synthesizing a nano-sized mesoporous zeolite beta composition, comprising: mixing silica, an aluminum source, tetraethylammonium hydroxide, and water to form an aluminum silicate fluid gel; heating the aluminosilicate fluid gel at a first temperature for a first period of time to form a zeolite beta product, wherein the first temperature is in a range of 100° C. to 150° C. and the first period of time is in a range of 2 days to 7 days; The zeolite beta product is hydrothermally treated under pressure and a second temperature for a second time period to prepare the nanosized mesoporous zeolite beta composition without using a structure directing agent, wherein the hydrothermal treatment uses steam, wherein the pressure is 1 bar to 5 bar, the second temperature is 400°C to 600°C, and the second time period is 0.5 hour to 5 hours, wherein the zeolite beta product is not calcined prior to the hydrothermal treatment, wherein the nanosized mesoporous zeolite beta composition has a pore volume of 1.0 mL / g to 1.5 mL / g, a pore diameter of 15 nm to 50 nm, and a relative crystallinity greater than 100%. 2 . The method of claim 1 , wherein the nanosized mesoporous zeolite beta composition has a particle size of 10 nm to 100 nm.

3. The method of claim 1, wherein the silicon dioxide comprises fumed silicon dioxide.

4. The method of claim 1, wherein the aluminum source is aluminum oxide.

5. The method according to claim 1, comprising: filtering the nanosized mesoporous zeolite beta composition; After the filtering, washing the nanosized mesoporous zeolite beta composition; drying the nanosized mesoporous zeolite beta composition at a third temperature for a third period of time after the washing; and After the drying, the nanosized mesoporous zeolite beta composition is calcined at a fourth temperature for a fourth period of time. 6 . The method of claim 5 , wherein the third temperature is in the range of 80° C. to 150° C., and the third time period is in the range of 3 hours to 8 hours. 7 . The method of claim 5 , wherein the fourth temperature is in a range of 500° C. to 600° C., and the fourth time period is in a range of 3 hours to 8 hours.

8. A method for hydrocracking a hydrocarbon feedstock, the method comprising: The hydrocarbon feedstock is contacted with a catalyst comprising a nanosized mesoporous zeolite beta composition under reaction conditions to convert a product stream containing at least 20 weight percent hydrocarbons having 1 to 4 carbon atoms, wherein the nanosized mesoporous zeolite beta composition is synthesized by a process comprising the steps of: mixing silica, an aluminum source, tetraethylammonium hydroxide, and water to form an aluminum silicate fluid gel; heating the aluminosilicate fluid gel at a first temperature for a first period of time to form a zeolite beta product, wherein the first temperature is in a range of 100° C. to 150° C. and the first period of time is in a range of 2 days to 7 days; The zeolite beta product is hydrothermally treated under pressure and a second temperature for a second time period to prepare the nanosized mesoporous zeolite beta composition without using a structure directing agent, wherein the hydrothermal treatment uses steam, wherein the pressure is 1 bar to 5 bar, the second temperature is 400°C to 600°C, and the second time period is 0.5 hour to 5 hours, wherein the zeolite beta product is not calcined prior to the hydrothermal treatment, wherein the nanosized mesoporous zeolite beta composition has a pore volume of 1.0 mL / g to 1.5 mL / g, a pore diameter of 15 nm to 50 nm, and a relative crystallinity greater than 100%.

9. The method of claim 8, wherein the nanosized mesoporous zeolite beta composition has a particle size of 10 nm to 100 nm.

10. The method of claim 8, wherein the silicon dioxide comprises fumed silicon dioxide.

11. The method of claim 8, wherein the aluminum source is aluminum oxide.

12. The method of claim 8, wherein the hydrocarbon feedstock comprises a heavy fraction having a boiling point greater than or equal to 540°C.

13. A nano-sized mesoporous zeolite beta composition comprising: A plurality of nanometer-sized mesoporous zeolite particles, each of the plurality of particles having a particle size of 10 nm to 100 nm, a pore volume of 1.0 mL / g to 1.5 mL / g, and a pore size of 15 nm to 50 nm, and a relative crystallinity greater than 100%, wherein the plurality of nanometer-sized mesoporous zeolite particles are synthesized by a method comprising the steps of: mixing silica, an aluminum source, tetraethylammonium hydroxide, and water to form an aluminum silicate fluid gel; heating the aluminosilicate fluid gel at a first temperature for a first period of time to form a zeolite beta product, wherein the first temperature is in a range of 100° C. to 150° C. and the first period of time is in a range of 2 days to 7 days; The zeolite beta product is hydrothermally treated at a pressure and a second temperature for a second time period to prepare the nanosized mesoporous zeolite beta composition without using a structure directing agent, wherein the hydrothermal treatment uses steam, wherein the pressure is 1 bar to 5 bars, the second temperature is 400° C. to 600° C., and the second time period is 0.5 hour to 5 hours, wherein the zeolite beta product is not calcined prior to the hydrothermal treatment.

Citation Information

Patent Citations

  • Zeolites, the production thereof, and their uses for upgrading heavy oils

    CN110621401A